DINAMIKA PERKEMBANGAN PEMUKIMAN PENDUDUK SETELAH TERJADI PEMEKARAN DI JORONG SUNGAI ARO NAGARI PAKAN RABAA KECAMATAN KOTO PARIK GADANG DIATEH KABUPATEN SOLOK SELATAN - Hendry, Joni - (STKIP PGRI Sumbar, 2014)
Focus problem in this study is how the dynamics of the residential community (development, population, settlement) in Jorong Sungai Aro Nagari Pakan Rabaa subdistrict Koto Parik Gadang Diateh district Solok Selatan. The purpose of this study was to determine the dynamics of the development of human settlements in Jorong Sungai Aro Nagari Pakan Rabaa subdistrict Koto Parik Gadang Diateh views of development, population and settlements. The research is a descriptive qualitative. Jorong Sungai Aro Nagari Pakan Rabaa subdistrict Koto Parik Gadang Diateh district Solok Selatan. Informants in this study is walinagari Sungai Aro, and community Sungai Aro. Data collection techniques using methods of observation, interviews, documentation methods. Analysis using data reduction, data presentation, and conclusion. The results showed that 1) the dynamics of the development of human settlements after separation) in Jorong Sungai Aro Nagari Pakan Rabaa subdistrict Koto Parik Gadang Diateh district Solok Selatan seen from accreting construction of school buildings is 2 pieces, 2 pieces of building a place of worship, and road construction. 2) In terms of the demographic population increase of more than half of the population since the expansion to the present, the addition of 70% of the indigenous people and migrants from outside is only 2%. 3) and the views of the settlement, the distance between the homes of 2-3 meters with a neighbors house, and the shape of the pattern groups